Accuracy of Clinical Diagnosis of Dementia with Lewy Bodies versus Neuropathology. - Skogseth, Ragnhild; Hortobágyi, Tibor; Soennesyn, Hogne; Chwiszczuk, Luiza; Ffytche, Dominic; Rongve, Arvid; Ballard, Clive; Aarsland, Dag (J Alzheimers Dis, 2017)
BACKGROUND: The first consensus criteria for dementia with Lewy bodies (DLB) published in 1996 were revised in 2005, partly because the original clinical criteria had suboptimal sensitivity. Few studies have assessed the accuracy of the 2005 criteria applied prospectively in newly diagnosed patients who have been followed longitudinally. OBJECTIVE: To explore the correlation between clinical and pathological diagnoses in patients with DLB and Parkinson's disease with dementia (PDD). METHODS: From a prospective referral cohort study with enriched recruitment of patients with DLB and PDD, we included the first 56 patients coming to autopsy. Patients had mild dementia at inclusion and were followed annually until death with standardized clinical assessments. Pathological assessment was performed blind to clinical information according to standardized protocols and consensus criteria for DLB. RESULTS: 20 patients received a pathological diagnosis of Lewy body disease; the corresponding clinical diagnoses were probable DLB (n = 11), PDD (n = 5), probable (n = 2) or possible (n = 2) Alzheimer's disease (AD). Of 14 patients with a clinical diagnosis of probable DLB, 11 had DLB/PDD and 3 had AD at pathology. One patient with clinically possible DLB fulfilled criteria for pathological AD. Sensitivity, specificity, positive predictive value, and negative predictive values for probable DLB were 73%, 93%, 79%, and 90%. CONCLUSION: Our findings suggest that the international clinical consensus criteria for DLB perform reasonably well. However, false positive and false negative diagnoses still occur, indicating that the criteria need to be improved, that biomarkers may be needed, and that neuropathological feedback is vital to improve accuracy.

Reduction of RPT6/S8 (a Proteasome Component) and Proteasome Activity in the Cortex is associated with Cognitive Impairment in Lewy Body Dementia. - Alghamdi, Amani; Vallortigara, Julie; Howlett, David R; Broadstock, Martin; Hortobágyi, Tibor; Ballard, Clive; Thomas, Alan J; O'Brien, John T; Aarsland, Dag; Attems, Johannes; Francis, Paul T; Whitfield, David R (J Alzheimers Dis, 2017)
Lewy body dementia is the second most common neurodegenerative dementia and is pathologically characterized by α-synuclein positive cytoplasmic inclusions, with varying amounts of amyloid-β (Aβ) and hyperphosphorylated tau (tau) aggregates in addition to synaptic loss. A dysfunctional ubiquitin proteasome system (UPS), the major proteolytic pathway responsible for the clearance of short lived proteins, may be a mediating factor of disease progression and of the development of α-synuclein aggregates. In the present study, protein expression of a key component of the UPS, the RPT6 subunit of the 19S regulatory complex was determined. Furthermore, the main proteolytic-like (chymotrypsin- and PGPH-) activities have also been analyzed. The middle frontal (Brodmann, BA9), inferior parietal (BA40), and anterior cingulate (BA24) gyrus' cortex were selected as regions of interest from Parkinson's disease dementia (PDD, n = 31), dementia with Lewy bodies (DLB, n = 44), Alzheimer's disease (AD, n = 16), and control (n = 24) brains. Clinical and pathological data available included the MMSE score. DLB, PDD, and AD were characterized by significant reductions of RPT6 (one-way ANOVA, p < 0.001; Bonferroni post hoc test) in prefrontal cortex and parietal cortex compared with controls. Strong associations were observed between RPT6 levels in prefrontal, parietal cortex, and anterior cingulate gyrus and cognitive impairment (p = 0.001, p = 0.001, and p = 0.008, respectively). These findings highlight the involvement of the UPS in Lewy body dementia and indicate that targeting the UPS may have the potential to slow down or reduce the progression of cognitive impairment in DLB and PDD.

Decreased Levels of VAMP2 and Monomeric Alpha-Synuclein Correlate with Duration of Dementia. - Vallortigara, Julie; Whitfield, David; Quelch, William; Alghamdi, Amani; Howlett, David; Hortobágyi, Tibor; Johnson, Mary; Attems, Johannes; O'Brien, John T; Thomas, Alan; Ballard, Clive G; Aarsland, Dag; et al. (J Alzheimers Dis, 2016)
Alpha-synuclein (α-syn) aggregations are the key pathological hallmark of dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), but are also frequently present in Alzheimer's disease (AD). Much remains unknown about the role of α-syn in the synapse and the wider role of synaptic dysfunction in these dementias. Changes in concentrations of key 'SNAP (Soluble N-ethylmaleimide Sensitive Factor Attachment Protein) Receptor' (SNARE) proteins as a consequence of alterations in the aggregation state of α-syn may contribute to synaptic dysfunction in patients with DLB, PDD, and AD and result in impaired cognition. We have studied a large cohort (n = 130) of autopsy confirmed DLB, PDD, AD, and control brains. Using semi-quantitative western blotting, we have demonstrated significant changes across the diagnostic groups of DLB, PDD, and AD in the SNARE and vesicle proteins syntaxin, Munc18, VAMP2, and monomeric α-syn in the prefrontal cortex, with a significant reduction of Munc18 in AD patients (p <  0.001). This correlated to the final MMSE score before death (p = 0.016). We also identified a significant negative correlation between the duration of dementia and the levels of the binding partners VAMP2 (p = 0.0004) and monomeric α-syn (p = 0.0002). Our findings may indicate that an upregulation of SNARE complex related proteins occurs in the early stages of disease as an attempt at compensating for failing synapses, prior to widespread deposition of pathological α-syn.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Amyloid beta-Peptides; Analysis of Variance; Cognition Disorders; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Regression Analysis; Synaptophysin; tau Proteins; Vesicle-Associated Membrane Protein 2